2005
DOI: 10.1097/01.mlg.0000168091.50584.b4
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) Transcripts in Malignant Inverted Papilloma are from Integrated HPV DNA

Abstract: HPV transcripts were present in SCC positive for HPV, and the relative level of E7 to E5 transcripts indicates integration of the viral genome. These findings are suggestive of HPV having an active role in the lesion. More extensive studies are needed to determine the exact role of HPV in IP and progression to SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 13 publications
1
51
1
2
Order By: Relevance
“…Nineteen of 20 HPV-positive IPs in our study showed HPV-11, and one showed HPV-6. These data were compared with the results of 22 published studies in which PCR was used for HPV detection [15,22,23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. As summarized in Table 2, a total of 720 IPs have been analyzed in previous studies, and HPV DNA was detected in 203 (28.1%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nineteen of 20 HPV-positive IPs in our study showed HPV-11, and one showed HPV-6. These data were compared with the results of 22 published studies in which PCR was used for HPV detection [15,22,23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. As summarized in Table 2, a total of 720 IPs have been analyzed in previous studies, and HPV DNA was detected in 203 (28.1%).…”
Section: Discussionmentioning
confidence: 95%
“…The malignant alteration of IPs has been widely recognized [1,4,8,22,23,[42][43][44][59][60][61][62][63][64][65]. Of all carcinomas associated with IPs, 61% are synchronous and 39%, metachronous [66].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using in situ hybridization detected HPV 6 and 11 in 42% of cases. In particular, IP associated with severe dysplasia or carcinoma and HPV 6 or 11 was present in 57 and 67% of tumors (42 (45). In particular, it was detected in two of three patients in which IP was associated with sinonasal SCC.…”
Section: Histopathologymentioning
confidence: 92%
“…SCC arising ex-inverted papillomas also reveal HPV RNA transcription, and evidence of viral integration [66]. [97].…”
Section: Hpv In Other Laryngeal Lesionsmentioning
confidence: 99%